2021
DOI: 10.1007/s40262-020-00976-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Semaglutide on the Pharmacokinetics of Levonorgestrel and Ethinylestradiol in Healthy Postmenopausal Women and Furosemide and Rosuvastatin in Healthy Subjects

Abstract: Background The first oral glucagon-like peptide-1 receptor agonist (GLP-1RA) comprises semaglutide co-formulated with the absorption enhancer, sodium N- (8-[2-hydroxybenzoyl] amino) caprylate (SNAC). Oral semaglutide may alter the pharmacokinetics of co-administered drugs via effects of semaglutide or SNAC. Two separate one-sequence crossover trials investigated the effects of oral semaglutide and SNAC on the pharmacokinetics of ethinylestradiol, levonorgestrel, furosemide and rosuvastatin. Methods Healthy, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Many individuals with T2D are required to take multiple medications [70]. Given the mechanism of action of oral semaglutide [56], which includes delayed gastric emptying [24], a number of studies have assessed the impact of oral semaglutide/SNAC on exposure to other commonly administered oral drugs [71][72][73]. In a pharmacokinetic study, co-administration of oral semaglutide with multiple (five) placebo tablets reduced the absorption of semaglutide [74].…”
Section: Interactions With Drugs Commonly Administered In Patients Wi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many individuals with T2D are required to take multiple medications [70]. Given the mechanism of action of oral semaglutide [56], which includes delayed gastric emptying [24], a number of studies have assessed the impact of oral semaglutide/SNAC on exposure to other commonly administered oral drugs [71][72][73]. In a pharmacokinetic study, co-administration of oral semaglutide with multiple (five) placebo tablets reduced the absorption of semaglutide [74].…”
Section: Interactions With Drugs Commonly Administered In Patients Wi...mentioning
confidence: 99%
“…Other pharmacokinetic studies have shown no clinically relevant interactions -indicating that no dose adjustments are required -when oral semaglutide is administered in people receiving lisinopril, warfarin, metformin, digoxin, furosemide, rosuvastatin, ethinylestradiol/levonorgestrel, or omeprazole [24,[71][72][73]. In a study of healthy subjects, concomitant administration of oral semaglutide 2 h after intake of omeprazole -which increases gastric pH -led to a 14% increase in the area under the curve (AUC) 0-24 h,Day10 of SNAC compared with administration of oral semaglutide alone, whereas SNAC maximum concentration and time to maximum concentration (t max ) were similar with and without omeprazole.…”
Section: Interactions With Drugs Commonly Administered In Patients Wi...mentioning
confidence: 99%
“…As semaglutide cause delayed gastric emptying, it can affect the pharmacokinetics of other co-administered drugs. Numerous cross-over trials confirmed non-interference of semaglutide with the bioavailability of oral contraceptives, lisinopril, metformin, warfarin, furosemide, digoxin, atorvastatin, rosuvastatin, and omeprazole [101][102][103][104][105]. Coadministration of levothyroxine with oral semaglutide results in increased exposure of levothyroxine by 33%.…”
Section: Drug Interactionsmentioning
confidence: 99%
“…An option to consider is to follow the dosing schedule for oral semaglutide when co-administered with levothyroxine and follow bedtime dosing schedules for levothyroxine in combination with increased monitoring of thyroid parameters [31][32][33]. Clinical assessments demonstrated that oral semaglutide had no significant effect on several other co-administered drugs [34]. Impact of Deviations from Preferred Oral Semaglutide Administration for Ramadan High inter-individual variability in gastrointestinal degradation of peptides, such as GLP-1RAs, might result in varying absorption rates of oral semaglutide if deviating from the optimized dosing schedule [27].…”
Section: Recommendations For Oral Semaglutide Dosing During Ramadan F...mentioning
confidence: 99%